(NoL_[ANSKIE PESNIs (NPESNIs - (Nf(B.(NrUBCOWs (NOB]AQ REDAKCIQs ((NlENINGRADs (NmOSKWAs 1971)
(NsBORNIK SOSTAWLEN IZ PESEN SELA oL_[A NA sMOLEN]INE STERTOGO S LICA ZEMLI WOJNOJ I WNOW_ WOSSTANOWLENNOGO IZ RUIN(B.s
Keywords: (NPESNIs